Can Common Business Practices Ever Be Anticompetitive? Redefining Monopolization. (18th March 2020) - Stylianou, Konstantinos
Abstract : For most of its modern history, antitrust law distinguished between normal competition and monopolization by looking for merit, legitimate business justifications, or efficiencies in the challenged business conduct. These proxies were seen as appropriate because they served antitrust law's welfare objectives well. However, the universal adoption of these proxies has overshadowed significant shortcomings, chief among them being that firms do not think in terms of legitimate business justifications or efficiencies, but rather in terms of long‐term sustainability and appropriation of value. As a result, antitrust law becomes detached from the very subjects it purports to regulate. Against the backdrop of the recent resurgence of enforcement activity, particularly involving tech giants, this article attempts a conceptualization of monopolization that does not revolve around merit in any form or function. Instead it introduces the proxy of commonness of business practices to determine their legality. This helps highlight the importance of considering "how things are done" in the relevant market, and helps reground antitrust law in business realities, which can enhance the heuristic mechanism of distinguishing between normal and anticompetitive practices. To prove this point the article develops an error test framework, through which it compares current tests with the proposed test in terms of their error footprint and concludes that the integration of the commonness parameter delivers better results. Ultimately, the inquiry undertaken herein is not only about constructing a conception of normal competition different from the only standard we currently have, that is, variants of merit, but also about shifting the conversation from how to fine‐tune existing standards to how to capture a more complete conception of competition.